ATP controls neuronal apoptosis triggered by microtubule breakdown or potassium deprivation. - Volbracht, C. (The Feinstein Institute for Medical Research, 1999)
BACKGROUND: Early loss of neurites followed by delayed damage of neuronal somata is a feature of several neurodegenerative diseases. Death by apoptosis would ensure the rapid removal of injured neurons, whereas conditions that prevent apoptosis may facilitate the persistence of damaged cells and favor inflammation and disease progression. MATERIALS AND METHODS: Cultures of cerebellar granule cells (CGC) were treated with microtubule disrupting agents. These compounds induced an early degeneration of neurites followed by apoptotic destruction of neuronal somata. The fate of injured neurons was followed after co-exposure to caspase inhibitors or agents that decrease intracellular ATP (deoxyglucose, S-nitrosoglutathione, 1-methyl-4-phenylpyridinium). We examined the implications of energy loss for caspase activation, exposure of phagocytosis markers, and long-term persistence of damaged cells. RESULTS: In CGC exposed to colchicine or nocodazole, axodendritic degeneration preceded caspase activation and apoptosis. ATP-depleting agents or protein synthesis inhibition prevented caspase activation, translocation of the phagocytosis marker, phosphatidylserine, and apoptotic death. However, they did not affect the primary neurite loss. Repletion of ATP by enhanced glycolysis restored all apoptotic features. Peptide inhibitors of caspases also prevented the apoptotic changes in the cell bodies, although the axodendritic net was lost. Under this condition cell demise still occurred 48 hr later in a caspase-independent manner and involved plasma membrane lysis at the latest stage. CONCLUSIONS: Inhibition of the apoptotic machinery by drugs, energy deprivation, or endogenous mediators may result in the persistence and subsequent lysis of injured neurons. In vivo, this may favor the onset of inflammatory processes and perpetuate neurodegeneration.